Kajian Spasial Rute Transportasi Angkutan Kota Dan Mobilitas Penduduk Menuju Pusat-Pusat Pelayanan Di Kota Padang - Sonia, Fira; Zuriyani, Elvi; Afryansih, Nila (Faculty Of Education, 2022)
The purpose of this study is to collect, process and analyze data and discuss angkot routes, patterns of population mobility to service centers and the potential for population movement in the city of Padang based on the population of the sample. This research method is a quantitative descriptive research. Because it examines the routes of public transportation and how the movement of people in the city of Padang to service centers and the potential for population movement. The population of this study is all public transportation routes in the city of Padang. The sample of this research is two routes, the angkot route code 201 and route code 419 with the longest route and the number of sub-districts that the angkot passes. The data analysis technique uses (GIS) and Newton's formula for spatial interaction. The results of the study are: 1). Angkot routes in the city of Padang have 87 routes/routes of various colors with a total of 2,604 vehicles. 2). The mobility of the population to the service center in the city of Padang using public transportation is divided into three stages, stage 1 the majority of passengers are students, stage 2 is the majority of passengers from the general public who are not students, stage 3 is the majority of passengers to the general public with the aim of going to the economic service center and the mobility of the population is commuter with a pattern of movement. spread out and return within a day. 3). Residents who have the potential for large movements are sub-districts that pass public transportation with route code 419 compared to the potential population in areas passed by public transportation with route code 201